Implementation Of The Polluter Pays Principle On Space Debris, Dylan Welmart - Welmart, Dylan Ritosa Theadiva; , Zunnuraeni; Pitaloka, Diva (Mataram Journal of International Law, 2023)
The study aims to examine the extent to which The Polluter-Pays Principle on the Space Debris problem can be applied. Moreover, this study analyzes the prevention and recovery for countries affected by cases of falling space objects resulting from the launch of a country or a space company to the Earth's surface, particularly in the territory of a country. This study uses the normative method. This study's results determine that the Polluter-Pays Principle can be applied to handling environmental pollution problems caused by Space Debris, especially Space Debris which causes damage and pollution on the surface of the Earth. Therefore, in the case of the fall of Space Debris in Indonesian territory that causes environmental damage and pollution, this principle may be applied. The aggrieved party may ask for compensation based on the Liability Convention and Article 7 of The Outer Space Treaty. The Liability Convention stipulates that the launching State bears absolute responsibility in paying compensation for damage caused by space objects on the surface of the Earth or aircraft, and is responsible for the damage due to his mistake in space. This responsibility action is used to protect, prevent and restore the environmental impact caused by the case of a space object falling into the territory of a country.